Antifungal activity of peppermint leaf essential oil (Mentha x piperita l.) against Microsporum gypseum and Microsporum canis - Setiawan, Glory Laura; Wijaya, Lorettha; Arieselia, Zita; Surja, Sem Samuel; Dewi, Rita (Pharmaciana, 2025)
Dermatophyte infections caused by Microsporum gypseum and Microsporum canis are common health issues affecting humans and animals. Peppermint leaves (Mentha x piperita L.) contain active constituents such as menthol and menthone, known for their antifungal potency. Authentication of Mentha piperita (peppermint) leaf in this study was performed through chemical profiling. The major constituents identified in peppermint essential oil include menthol, pulegone, isopulegol, limonene, and methylene. The purpose of this study was to examine the potency of peppermint leaf distillation essential oil in inhibiting the growth of M. gypseum and M. canis at concentrations of 25%, 12.5%, 6.25%, 3.125%, 1.562%, 0.781%, 0.390%, and 0.195%. Microdilution standard method was used to examine the Minimum Inhibitory Concentration (MIC). Antifungal potency was assessed based on medium turbidity, compared to itraconazole as a positive control. Results showed that peppermint essential oil at a concentration of 6.25% and 1.562% inhibited the growth of M. gypseum and M. canis, respectively. Therefore, peppermint leaf essential oil can be recommended as a natural antifungal agent against M. gypseum and M. canis.